The Distribution Coefficients of Major and Minor Elements in Coral Skeletons Under Variable Calcium Seawater Concentrations - Ram, Sharon; Erez, Jonathan (Frontiers in Earth Science, 2021)
Corals are one of the best archives for past ocean seawater (SW) chemistry and isotopes. However, the distribution coefficients of major and minor elements in coral skeletons are not well determined. In this study, we launched an experiment to determine the distribution coefficients of multiple elements in corals’ skeletons by changing Ca concentrations in SW (CaSW). Two scleractinian corals, Pocillopora damicornis and Acropora cervicornis were cultured in modified Gulf of Eilat, Red-Sea water with CaSW of approximately 10, 15, 20, and 25 mM. After approximately three months, the newly grown skeletons were analyzed for the following elements: Li, Na, Mg, K, Sr and Ba. Their ratios to Ca in the coral skeleton (Cacoral) increased linearly with El/CaSW (with R2 values above 0.98), crossing the origin and thus indicating constant distribution coefficient for each element over the experimental range of El/CaSW. The values of DEl were in good agreement with values reported for corals collected in natural seawater. However, differences were observed between the two species, and both were slightly deviating from inorganic aragonite D values. These deviations are well explained by Rayleigh fractionation process in the calcifying fluid (assuming it is mainly seawater). This was observed both for elements with D>1 (Ba and Sr) and D<1 (Li, Mg, Na and K). P. damicornis showed open system behavior (~20% of its Ca utilized) while A. cervicornis showed more closed calcifying reservoir (~50% of its Ca utilized). This approach should help in the reconstruction of past seawater chemistry based on multielement measurements in fossil corals. In particular, Na/Cacoral can be used to reconstruct past ocean Ca concentrations and with El/Cacoral ratios for other elements, their concentrations for the Cenozoic can be reconstructed.